2019
DOI: 10.1111/1756-185x.13662
|View full text |Cite
|
Sign up to set email alerts
|

Risk of opportunistic infections in patients with antineutrophil cytoplasmic antibody‐associated vasculitis, using a Japanese health insurance database

Abstract: Aim:Opportunistic infections (OIs) adversely affect outcomes in patients with antineutrophil cytoplasmic antibody-associated vasculitis (AAV). This study aimed to identify the incidence proportion of risk factors for OIs in patients with AAV who were on remission-induction therapy, using a Japanese health insurance database.Method: This retrospective longitudinal population-based study was conducted using claims data provided by Medical Data Vision Co., Ltd. We defined individuals as AAV cases receiving remiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…5 Population-based studies are less prone to selection bias and allow long-term follow-up of relatively rare conditions and can thus enhance our limited understanding of OI in lupus. 3,7,12,13 Based on the above, we performed a population-wide long-term study into the rate and changes over time for overall and organism specific hospital admission for OI among lupus patients in Western Australia (WA) during a period (1985–2015) where more intensive and targeted immunomodulation for lupus gradually became embedded in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…5 Population-based studies are less prone to selection bias and allow long-term follow-up of relatively rare conditions and can thus enhance our limited understanding of OI in lupus. 3,7,12,13 Based on the above, we performed a population-wide long-term study into the rate and changes over time for overall and organism specific hospital admission for OI among lupus patients in Western Australia (WA) during a period (1985–2015) where more intensive and targeted immunomodulation for lupus gradually became embedded in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Prednisolone use was identified as a risk factor for CMV infection. 47,49 In their multivariate analysis, Sakai et al 49 underlying rheumatic disease (P < 0.01). They also found that their patients with symptomatic CMV infection received higher average prednisolone doses compared with their non-symptomatic counterparts (median 32, range 4-100 mg/day vs. median 20, range 1-50 mg/day, P < 0.01).…”
Section: Treatmentmentioning
confidence: 99%
“…Patient demographics Age (for any opportunistic infection) 49 Male 47 Laboratory characteristics Lymphopenia or decreases in lymphocyte count over 4 weeks 47,48 Albumin <30 g/L or decreases in albumin over 4 weeks 48 Lower CD4 + T-cell count 47 Higher LDH, BUN levels 47…”
Section: Significant Risk Factors For CMV Infection In Patients With ...mentioning
confidence: 99%
“… 5 In France, dexamethasone is now the standard of care in patients hospitalized with moderate to severe COVID‐19 pneumonia associated with excessive systemic inflammation. 6 However, corticosteroids in this context may be associated with delayed viral clearance such as observed in other coronavirus‐induced severe pneumonia, 7 , 8 , 9 increased opportunistic infection, 9 , 10 hyperglycemia 11 and other side effects. Data are still lacking on the precise timing of initiation and practical use of dexamethasone in COVID‐19.…”
Section: Introductionmentioning
confidence: 99%